CONTROLS ON THE DISTRIBUTION AND ISOTOPIC COMPOSITION OF HELIUM IN DEEP GROUND-WATER FLOWS - Zhao X.; Fritzel T.L.B.; Quinodoz H.A.M.; Bethke C.M.; Torgersen T. (My University, 1998)
The distribution and isotopic composition of helium in sedimentary basins can be used to interpret the ages of very old ground waters. The piston-flow model commonly used in such interpretation, however, does not account for several important factors and as such works well only in very simple flow regimes. In this study of helium transport in a hypothetical sedimentary basin, we develop a numerical model that accounts for the magnitude and distribution of the basal helium flux, hydrodynamic dispersion, and complexities in flow regimes such as subregional flow cells. The modeling shows that these factors exert strong controls on the helium distribution and isotopic composition. The simulations may provide a basis for more accurate interpretations of observed helium concentrations and isotopic ratios in sedimentary basins.